Thermal Analysis of Natural Convection in an Annular enclosure partially filled with metal foam: A Numerical Study Using ANSYS Fluent (Journal of Engineering, 2025)
In this study presents a numerical investigation of natural convection heat transfer in an annular enclosure partially filled with metal foam. The inner cylinder is maintained at a constant temperature, while the outer cylinder is subjected to a uniform heat flux; both vertical sidewalls are thermally insulated. The fluid flow is modeled using the Navier–Stokes equations under the Boussinesq approximation, and the porous medium is described by the Brinkman–Forchheimer Darcy model, assuming local thermal equilibrium. Simulations are conducted using ANSYS FLUENT to examine the effects of pore density (10 PPI and 40 PPI), inclination angle (0°, 30°, 60°, 90°) and Rayleigh number (10⁴ ≤ Ra ≤ 10⁶) on thermal performance. Results indicate that the presence of metal foam significantly enhances heat transfer compared to the clear fluid case. The Nusselt number increases with both Rayleigh number and the inclination angle. Notably, the 10 PPI foam increases the average Nusselt number by approximately 50%, while the 40 PPI foam shows a 33% improvement compared to the clear fluid case. In all cases, temperature rises with increasing Rayleigh number, indicating stronger natural convection. Moreover, increasing the inclination angle from the horizontal configuration enhances heat transfer, with the most significant improvement between 60° to 90°.